1981
DOI: 10.1007/bf01114797
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic lipogenesis in starved and diabetic animals by thyroid hormone

Abstract: The effects of intragastric feeding with glucose and of the administration of L-triiodothyronine (T3) on in vivo rates of hepatic lipogenesis were investigated in control (fed ad libitum on normal diet), diabetic (fed ad libitum on normal diet), fat-fed (fed ad libitum on high-fat diet), and starved (food removed for 48 h) rats. Two days of T3 treatment increased hepatic lipogenesis in control and fat-fed animals but not in the diabetic or starved animals, although increases in lipogenesis in diabetic animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Consequently, lipogenesis is decreased in rodent models of T1D [93]. Nonetheless, patients with untreated T1D have decreased lipoprotein clearance and hypertriglyceridemia [94,95]; those with poorly controlled T1D also have hypercholesterolemia, and increased VLDL-cholesterol and LDL-cholesterol [96,97].…”
Section: The Diabetic Dyslipidemiamentioning
confidence: 99%
“…Consequently, lipogenesis is decreased in rodent models of T1D [93]. Nonetheless, patients with untreated T1D have decreased lipoprotein clearance and hypertriglyceridemia [94,95]; those with poorly controlled T1D also have hypercholesterolemia, and increased VLDL-cholesterol and LDL-cholesterol [96,97].…”
Section: The Diabetic Dyslipidemiamentioning
confidence: 99%
“…Liver is a major organ for lipogenesis, where most lipogenic genes, including the fatty acid synthase (FAS), stearoyl-CoA desaturase-1 (SCD1) and long chain free fatty acid elongase (FAE), are highly expressed. Several nuclear receptors have been implicated in lipid homeostasis, such as the liver X receptors (LXRs) [1], thyroid hormone receptor (TR) [2] and peroxisome proliferator-activated receptors (PPARs). Both LXRα and LXRβ have been shown to promote lipogenesis though direct and indirect mechanism [1], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…In rat liver, thyroid-hormone administration increased lipogenesis and the activities of key lipogenic enzymes such as acetyl-CoA carboxylase and fatty acid synthase (Diamant et al 1972; Roncari & Murthy, 1975;Volpe & Marasa,. 1975;Gnoni et al, 1980;Sugden et al, 1981Sugden et al, , 1983, whereas thyroidectomy or propylthiouracil treatment decreases fatty acid synthase activity (Baquer et al, 1976;Gnoni et al, 1980). By contrast, although it is generally found that hyperthyroidism and hypothyroidism also increase and decrease respectively these parameters in white adipose tissue (Diamant et al, 1972;Volpe & Marasa, 1975;Baquer et al, 1976;Gnoni et al, 1980), the amplitude of these changes is smaller than in liver, and Roncari & Murthy (1975) have even reported a decrease in acetyl-CoA carboxylase, fatty acid synthase and lipogenic rate in vivo in white fat on thyroid-hormone administration.…”
Section: Introductionmentioning
confidence: 99%